Porous Silk Scaffold Derived from Formic Acid: Characterization and Biocompatibility - Ting Zhang; Qianwei Xiong; Yuxi Shan; Feng Zhang; Shijun Lu (Advances in Materials Science and Engineering)
Silk porous scaffold possesses 3D space structure for cell adhesion and tissue growth and demonstrates promising applications in biomedical engineering. In this study, a porous silk scaffold was prepared from formic acid, and its morphology, structure, mechanical properties, and biocompatibility were characterized. The preparation process involved silk dissolution in formic acid and salt leaching in water, avoiding widely used organic solvent-induced crystallization including methanol or ethanol. The resulting porous silk scaffolds showed good pore structure, stable silk II crystalline structure, good mechanical properties, and enhanced cell biocompatibility. Therefore, these findings demonstrate that porous silk scaffold derived from formic acid has great potential applications as 3D scaffold for cell culture and tissue repair.